Investment decisions modelling along sustainable development concept on financial markets - Rutkauskas, Aleksandras Vytautas; Miečinskienė, Algita; Stasytytė, Viktorija (Technological and Economic Development of Economy, 2008)
The goal of the paper is development of the conception of sustainable return investment decisions strategy in capital and money markets and modeling of investment decisions along sustainable development concept in capital and money markets. The research was performed with an experiment in FOREX and in some matured and emerging capital markets. The adequate for investments decisions reliability assessment portfolio will be presented and analysed as main instrument for developing sustainable return investment decisions strategy. The cases of practical implementation of adequate portfolio will be widely described. Further, the pragmatical problems how to use the strategy as innovative and effective financial instrument for investors and stock treasury will be discussed. Practical calculation was made on the very last data of different markets.Investicinių sprendimų modeliavimas vartojant tvariosios plėtros sąvoką finansų rinkoseSantrauka. The goal of the paper is development of the conception of sustainable return investment decisions strategy in capital and money markets and modeling of investment decisions along sustainable development concept in capital and money markets. The research was performed with an experiment in FOREX and in some matured and emerging capital markets. The adequate for investments decisions reliability assessment portfolio will be presented and analysed as main instrument for developing sustainable return investment decisions strategy. The cases of practical implementation of adequate portfolio will be widely described. Further, the pragmatical problems how to use the strategy as innovative and effective financial instrument for investors and stock treasury will be discussed. Practical calculation was made on the very last data of different markets.Reikšminiai žodžiai: tvarioji investavimo strategija, rinkos elgsena, adekvatus portfelis, pelningumo, patikimumo ir rizikos subendramatinimas.First published online: 21 Oct 2010